Osteogenesis-Related Long Noncoding RNA GAS5 as a Novel Biomarker for Osteonecrosis of Femoral Head - Liu, Guanzhi; Luo, Sen; Lei, Yutian; Jiao, Ming; Cao, Ruomu; Guan, Huanshuai; Tian, Run; Wang, Kunzheng; Yang, Pei (Frontiers in Cell and Developmental Biology, 2022)
Background:The lack of effective biomarkers makes it difficult to achieve early diagnosis and intervention for osteonecrosis of femoral head (ONFH). Hence, we aimed to identify novel long noncoding RNA (lncRNA) biomarkers for ONFH. Methods: High-throughput RNA sequencing was performed to detect lncRNA and mRNA expression levels in subchondral bone samples from three patients with ONFH and three patients with femoral neck fractures. Integrated bioinformatics analyses were conducted to identify lncRNAs associated with ONFH development and their potential functions and signaling pathways. A co-expression network was constructed based on the gene time-series expression data in GSE113253. After selecting lncRNA GAS5 as a novel biomarker for ONFH, bone marrow mesenchymal stem cell (BMSC) osteogenic differentiation assays were performed to verify the association between lncRNA GAS5 and osteogenic differentiation. Alkaline phosphatase (ALP) staining and quantitative reverse-transcription polymerase chain reaction (RT-qPCR) were used to measure the osteogenic phenotype and lncRNA GAS5 expression. Finally, for further validation, ONFH rat models were established and lncRNA GAS5 expression in subchondral bone was detected by RT-qPCR. Results: We identified 126 and 959 differentially expressed lncRNAs and genes, respectively. LncRNA GAS5 expression level was significantly downregulated in patients with ONFH compared to the control group patients. The BMSC osteogenic differentiation assays showed that ALP activity increased gradually from day 3 to day 7, while lncRNA GAS5 expression level was significantly upregulated in the osteogenic differentiation induction groups. Furthermore, in vivo experiments suggested that the bone volume/tissue volume value and trabecular thickness significantly decreased in the ONFH rat model group compared to the control group, whereas the trabecular space significantly increased in the ONFH group compared to the control group. In addition, lncRNA GAS5 expression level significantly decreased in the ONFH rat model group. Conclusion: LncRNA GAS5 expression level was highly associated with BMSC osteogenic differentiation and was significantly downregulated in both the subchondral trabecular bone tissue from ONFH patients and ONFH rat models. Therefore, lncRNA GAS5 can serve as an ONFH osteogenic biomarker to provide an effective target for early diagnosis and molecular therapy of ONFH.